Is spontaneous echo contrast associated with device-related thrombus or embolic events after left atrial appendage occlusion?: insights from the multicenter German LAARGE registry - Fastner, Christian; Müller, Claus; Brachmann, Johannes; Lewalter, Thorsten; Akın, Ibrahim; Sievert, Horst; Käunicke, Matthias; Zeymer, Uwe; Hochadel, Matthias; Schneider, Steffen; Senges, Jochen; Erkapic, Damir; et al. (Journal of interventional cardiac electrophysiology, 2024)
Interventional left atrial appendage occlusion (LAAO) provides an alternative to oral anticoagulation (OAC) for prophylaxis of thromboembolic events (TEs) in nonvalvular atrial fibrillation patients, predominantly in those with high bleeding risk and contraindications for long-term OAC. Although spontaneous echo contrast (SEC) is a well-known risk factor for atrial thrombus formation, little is known about whether this means an increased risk of device-related thrombus (DRT) or TEs following LAAO.